“Race”, ethnic and genetic adscription in Uruguay - Sans, Mónica (2009)
Native Americans, Africans and Europeans formed, to varying degrees, the Uruguayan population. At the beginning of the 19 th century, census data indicated that the country was comprised of 36% African or African descended inhabitants, while the number of Natives was not determined. After this, there is no available information on the origins of the population, with the exception of foreigners. In 1996-1997, a Household Survey asked Uruguayans to self-identify their “race”, and in 2006, their ancestry. The first survey showed that 5.9% of the populations was “black or mixed-black” and 0.4% was Native or Native-descended, while the percentages of individuals who claimed African or Native ancestry increased to 9.1% and 4.5% respectively. Genetic data demonstrate that there is a contribution of 6% of African and 10% of Native American blood in the population, while maternal ancestry increases these values to 10% and 31% respectively. Census and genetic data are discussed in relation to national identity.